What is the impact of personal care products selection on greywater characteristics and reuse? - Kadewa, Wilfred W.; Knops, Geraldine; Pidou, Marc; Jeffrey, Paul; Jefferson, Bruce; Le Corre, Kristell S. (Elsevier, 2020)
Accounting for up to three quarters of the wastewater volume resulting from domestic activities but containing only a third of its organic content, greywater is seen as an alternative water source for non-potable reuse. This unique study explores the question whether consumers' product selection could affect the treatability and reuse of bathroom greywater. Fifty five personal care and household products (PCHP) were analysed for their effects on a range of water quality parameters including their aquatic and soil toxicity using Microtox® and MicroResp™. The organic content of these PCHPs varied considerably, not only from one category to another (0.2 gTOC.L−1 for hair conditioners to 2.7 gTOC.L−1 for toothpastes), but also within each category (0.1 gTOC.L−1 to 3.6 gTOC.L−1 amongst the shampoos). As expected, the PCHPs' macronutrient content was low, suggesting some limitation towards biological treatment of bathroom greywater. Regarding the impact of product selection on toxicity towards aquatic and soil microorganisms, the results revealed a higher sensitivity of Vibrio fischeri to the individual PCHPs than the MicroResp™ soil microorganisms. In the latter case, 75% of the products caused a stimulation response from the microorganisms although some decreases in basal respiration were observed for specific PCHPs within product categories. However, based solely on MicroResp™, the short-term discharge of treated bathroom greywater, regardless of consumer product selection, is unlikely to have a negative impact on soil microbial activity. Overall, the work has demonstrated the importance of consumer choice on the pollution load and treatability of greywater. However, no clear link between greywater characteristics and factors that normally determine consumer product selection (branding, type) were identified. This means it is not currently possible for consumers to actively manage the issue through choice such that process designers and technology developers must ensure technologies are sufficiently robust to manage the potential variations that could occur.
Keywords: Greywater; Recycling; Personal care products; Consumers choice; Physico-chemical characterisation; Microbiological soil and aquatic toxicity